PEP uP (Enhanced Protein‐Energy Provision via the Enteral Route Feeding Protocol) in Surgical Patients—A Multicenter Pilot Randomized Controlled Trial. Issue 2 (11th February 2019) - Yeh, D. Dante; Ortiz, Luis Alfonso; Lee, Jae Moo; Chan, Jeffrey; McKenzie, Katherine; Young, Brian; Chetelat, Lindsay; Collier, Bryan; Benson, Andrew; Heyland, Daren K.
Abstract: Background: The Enhanced Protein‐Energy Provision via the Enteral Route Feeding Protocol (PEP uP) has been shown to be feasible, safe, and effective in delivering significantly more energy/protein, though it has not been well studied in surgical/trauma patients. We hypothesized that PEP uP will effectively increase energy/protein delivery to critically ill surgical/trauma patients. Methods: This multicenter, prospective, randomized pilot study included adult patients admitted to surgical service who were expected to require mechanical ventilation for >24 hours and intensive care unit (ICU) care for >72 hours. Subjects were randomized to PEP uP or standard care. The PEP uP protocol includes initiation at goal rate, semi‐elemental formula, prophylactic prokinetic agents, 24‐hour volume‐based goals, and modular protein supplementation. The primary outcome was nutrition adequacy over the first 12 ICU days. Results: Thirty‐six subjects were enrolled. Slow recruitment resulted in early trial termination by the sponsor. There were no baseline differences between groups. PEP uP patients received more protein (106.8 ± 37.0 vs 78.5 ± 30.3 g/d, P = 0.02). Energy delivery was not significantly different (1400.0 ± 409.5 vs 1237.9 ± 459.1 kcal, P = 0.25). Vomiting was more common in the PEP uP patients (32% vs 12%, P = 0.03). PEP uP protocol violations included 2 patients (15.4%) not receiving pro‐motility medications, 3 (23.1%) not receiving volume‐based feeds as ordered, and 4 (30.8%) not receiving supplemental protein. Conclusions: In surgical/trauma patients, PEPuP seemed to improve protein delivery but was difficult to implement successfully and may increase vomiting rates.